Migration, Gender and Social Justice : Perspectives on Human Insecurity. - Truong, Thanh-Dam.; Gasper, Des.; Handmaker, Jeff.; Bergh, Sylvia I. (Berlin, Heidelberg : Springer Berlin / Heidelberg, 2013)
This book synthesises research projects in Asia, Africa and Latin America to examine the forces driving the 'feminization' of migration, its consequences and the range of contemporary attempts to conceptualize and promote the human rights of migrant women.
10.6 Conclusions.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books